Dampak Perubahan Harga Beras terhadap Kesejahteraan Petani: Studi Kasus Nagari Panyakalan Kabupaten Solok - Silvia, Engla Desnim; Susanti, Rina; Ariani, Fatma; Yunus, Mukhlis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The high level of agricultural production in Solok Regency has not been in line with the increase in farmers' welfare. In fact, the level of farmer welfare is an important factor in the development of the agricultural sector. The aim of this research is to determine the impact of changes in rice prices on farmer welfare using a case study approach. Data collection techniques include interviews, observation and documentation. For technical data analysis through percentage analysis. This research revealed that 59.2% of farmers before the increase in rice prices had a good economic condition, however, when the price of rice increased, the economic condition of rice farmers became less good, amounting to 66.3%. Apart from that, some farmers stated that their income increased by a percentage of 9.2%. The increase in rice prices does not result in the consumption patterns of farming communities decreasing, farmers reduce rice consumption and use other foods that contain carbohydrates as substitute foods.